Muslim American Voices: Saba Fathima’s Attitudinal Position in TEDx Talks - Nailafidah, Salsabiila; Handayani, Tuty (Lexicon, 2024)
This study examines the appraisal system of Saba Fathima’s speech “Making Spaces for Muslim Voices” at TEDx Talk to understand Fathima’s attitude regarding the Muslim American voices. Utilizing the qualitative approach, this study employs Martin and White’s Appraisal Theory. It collects the data by dividing the speech into clauses and examines them based on three elements of appraisal’s attitude such as affect, judgment, and appreciation. The attitude can also be divided into positive and negative attitude. The findings demonstrate that the most common attitude used by Saba Fathima is judgement (55%), followed by affect (41%) and appreciation (4%). It implies that Fathima prefers to show the assessment of experience she faced as Muslim American rather than emphasizing her appreciation. Additionally, she shows more positive attitude than the negative one, implying her optimism toward the future of Muslim American. The study shows how Saba Fathima strategically arranges the words and structures her speech to build an interpersonal relationship with her audiences. By carefully selecting the diction, she effectively communicates her messages and thoughts, influences the audience’s perspective, and creates meaningful interactions. This study also highlights her ability to convey a shared responsibility in addressing the issues faced by Muslim Americans. In conclusion, the study underscores the importance of rhetorical strategies in producing persuasive and impactful speeches.